Government Spending in Education and Economic Growth in Cameroon: A Vector Error Correction Model Approach - DOUANLA, Tayo Lionel; ABOMO, Fouda Marcel Olivier (Journal of Research in Educational Sciences, 2015)
This study aims at assessing the effect of government spending in education on economic growth in Cameroon over the period 1980-2012 using a vector error correction model. The estimated results show that these expenditures had a significant and positive impact on economic growth both in short and long run. The estimated error correction model shows that an increase of 1% of the growth rate of private gross fixed capital formation and government education spending led to increases of 5.03% and 10.145 % respectively in the long-run on economic growth. Education spending thus appears as one of the main driving force of the economic growth process in Cameroon.